(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, we delve deeper into the nuanced portrayals of princesses in Western literature. The enduring appeal of princesses in Western novels lies in their ability to embody both traditional and subversive qualities, reflecting the diverse roles and expectations placed on women throughout history.